The Relationship between Antenatal Care with Childbirth Complication in Indonesian’s Mothers (Data Analysis of The Indonesia Demographic and Health Survey 2012) - Bantas, Krisnawati; Aryastuti, Nurul; Gayatri, Dwi (UI Scholars Hub, 2018)
Labor complications often lead to maternal death. A good antenatal care can reduce maternal and infant mortality. The purpose of this study was to analyze the relationship between antenatal care and labor complica tion among Indonesian’s mothers. Data of the Indonesia Demographic and Health Survey (IDHS) 2012 from 33 Provinces were used in this study. Samples consisted of 11.803 women aged 15-49 years who deliv ered baby at sometimes during the last 5 years before survey. A cross sectional design was used. Variables in the study consisted of dependent variable (labor complication), main independent variable (antenatal care) and potential confounder variables including maternal age in the last labor, mother’s education, number of parity, preceding birth interval, birth attendance, place of delivery, a history of pregnancy complications, history of previous labor complication and multiple pregnancies. A logis tic regression was used for analyzing data. Results of this study showed that the prevalence of labor complications was 49.2% and the preva lence of poor antenatal cares (do not use a standard criteria recom mended by Indonesian Health Ministry) was 91.2%. After controlling for all potential confounder variables, this study showed that, mothers with a poor antenatal care had a 1.3 times higher risk of labor complications than mothers with a good antenatal care (POR 1.3, 95% CI: 1.1 - 1.4)